Spionidae (Annelida: ‘Polychaeta’: Canalipalpata) from Lizard Island, Great Barrier Reef, Australia: the genera Malacoceros, Scolelepis, Spio, Microspio, and Spiophanes - Meißner, Karin; Götting, Miriam (Zootaxa, 2015)
Seven species belonging to the spionid genera Malacoceros, Scolelepis, Spio, Microspio, and Spiophanes were found during the polychaete workshop on Lizard Island in August 2013. One species is new to science and named Scolelepis inversa n. sp., another Scolelepis species is probably also a new species but was represented in our samples by only a single specimen and not formally described. All other species have been reported previously from Australia. Species diagnoses of all species found during the workshop and of Scolelepis balihaiensis Hartmann-Schröder, 1979, Microspio microcera (Dorsey, 1977) and M. minuta (Hartmann-Schröder, 1962) have been critically reviewed and amended based on the study of type material. The potential synonymy of Microspio minuta (Hartmann-Schröder, 1962) and M. microcera (Dorsey, 1977) is discussed. The new combination Spio jirkovi (Sikorski, 1992) proposed by Sikorski (2013) is returned to Malacoceros. We added DNA barcodes for five species collected in the Lizard Island area to public databases which will be useful in future phylogenetic and phylogeographic studies. For Microspio we provide the first sequence data for this genus.